RELIGIOUS BROTHERS’ EMOTION REGULATION TO PURSUE WELL-BEING IN ONLINE LEARNING - Nahak, Yulius; Budiharajo, Markus (Universitas Pelita Harapan, 2022)
Effective learning is supported by a conducive environment. However, pandemic situations with their demands have changed the learning system from face-to-face to a virtual learning environment, which in some ways affects the emotions of the students. This study aimed to investigate the way undergraduate students regulate their emotions to pursue well-being in online learning challenges. Two research questions were proposed, namely (1) how do the undergraduate students manage their emotions to cope with the online learning challenges; and (2) what factors did they find facilitative to cope with the challenges? Qualitative research was utilized through semi-structured interviews. The respondents were two first-year and two fourth-year undergraduate students from 2 private universities in Yogyakarta, Indonesia. The result indicated that community context as an ecological perspective provides security, trust, and meaningful activities that help its members cope with their negative emotions to pursue well-being in online learning. Furthermore, the school context played a crucial role in facilitating the learning goals through various supports and strategies. The lecturers and future researchers are expected to emphasize and develop more empirical studies concerning the importance of self-regulation of emotion to attain well-being in online learning challenges. BAHASA INDONESIA ABSTRAKPembelajaran yang efektif didukung oleh lingkungan yang kondusif. Namun, situasi pandemi dan tuntutannya telah mengubah lingkungan pembelajaran dari tatap muka menjadi pembelajaran virtual, yang berdampak pada emosi siswa dalam beberapa hal. Studi ini bertujuan untuk menyelidiki cara mahasiswa sarjana mengatur emosi mereka untuk mengejar kesejahteraan dalam tantangan pembelajaran online. Dua pertanyaan penelitian diajukan, yaitu (1) bagaimana mahasiswa sarjana mengelola emosi mereka untuk mengatasi tantangan pembelajaran online; dan (2) faktor apa saja yang mereka temukan fasilitatif untuk mengatasi tantangan pembelajaran online? Penelitian kualitatif digunakan dalam studi ini melalui wawancara semi-terstruktur. Respondennya adalah dua mahasiswa sarjana tahun pertama dan dua mahasiswa sarjana tahun keempat dari 2 universitas swasta di Yogyakarta, Indonesia. Hasilnya menunjukkan bahwa konteks komunitas religius sebagai perspektif ekologis memberikan keamanan, kepercayaan, dan kegiatan yang bermakna yang membantu anggotanya mengatasi emosi negatif mereka untuk mengejar kesejahteraan dalam pembelajaran online. Selain itu, konteks universitas memainkan peran krusial dalam memfasilitasi tujuan pembelajaran melalui berbagai dukungan dan strategi. Para dosen dan peneliti masa depan diharapkan untuk menekankan dan mengembangkan studi yang lebih empiris mengenai pentingnya regulasi emosi untuk mencapai kesejahteraan dalam tantangan pembelajaran online.